Capital structure and corporate strategy in South Africa an empirical analysis - Chen, Haoyu (School of Economics, 2023)
Using South African data, this study tests three propositions about capital structure and product market strategy. The results support the hypotheses that oligopolists have relatively high debt-equity ratio; their debt tends to be long term; and firms that produce unique and / or durable goods tend to have less debt-equity ratio.